PERAN MEDIASI PENGENDALIAN INTERNAL DAN BUDAYA ETIS TERHADAP TINDAKAN FRAUD - Fadly Chandra; Suwandi NG; Cherly Tanamal (Media Riset Akuntansi, Auditing & Informasi, 2021)
The purpose of this study was to investigate the role of ethical culture mediation and internal control in the relationship between anti-fraud investment and fraud in the banking sector in Makassar. The research sample used purposive sampling method. The data collection technique used a survey method with a questionnaire. The population of this study were managers or heads of departments who worked in banking companies in Makassar with a total of 120 respondents. Path analysis and sobel test were used to test this hypothesis. The results of this study indicate that the perceived increase in anti-fraud investment has a positive effect on the mediating variables of ethical culture and internal control. Ethical culture mediates the negative and significant influence between anti-fraud investment and fraud. These findings imply that investing in an ethical culture is more effective in preventing fraud.